Association of family history of cardiovascular disease with the prevalence of cardiometabolic risk factors in young adults in the United Arab Emirates: The UAE healthy future study - Fatima Mezhal; Amar Ahmad; Abdishakur Abdulle; Andrea Leinberger-Jabari; Abdulla AlJunaibi; Abdulla Alnaeemi; Ayesha S. Al Dhaheri; Eiman AlZaabi; Fatma Al-Maskari; Fatme AlAnouti; Juma Alkaabi; Marina Kazim; et al. (PLoS ONE, 2025)
Introduction Family history of cardiovascular disease (CVD) is an independent risk factor for coronary heart disease, and the risk increases with number of family members affected. It offers insights into shared genetic, environmental and lifestyle factors that influence heart disease risk. In this study, we aimed to estimate the association of family history of CVD and its risk factors, as well as the number of affected parents or siblings, with the prevalence of major cardiometabolic risk factors (CRFs) such as hypertension, dysglycemia, dyslipidemia and obesity in a sample of young adults. Methods The study utilized a cross-sectional analysis of baseline data from the UAE Healthy Future Study (UAEHFS), involving 5,058 respondents below the age of 40 years. Information on parental and sibling health regarding heart disease and stroke, hypertension, type 2 diabetes (T2D), high cholesterol and obesity, was gathered through a self-completed questionnaire. CRFs were estimated based on body measurements, biochemical markers and self-reported conditions. Multivariate regression analyses were used to examine the associations between categories of family history and the estimated CRFs. Results More than half (58%) of the sample reported having a positive family history of CVD or its risk factors. The most common family history reported was T2D and hypertension, which accounted for 39.8% and 35% of the sample, respectively. The prevalence of all CRFs was significantly higher among those with a positive family history compared to those without family-history (P < 0.001). The prevalence and likelihood of having a CRF increased as the number of parents and/or siblings affected increased, indicating a potential dose-response trend. The odds were highest among individuals with both parental-and-sibling family history of disease, where they increased to 2.36 (95% CI 1.68-3.32) for hypertension, 2.59 (95% CI 1.86-3.60) for dysglycemia, 1.9 (95% CI 1.29-2.91) for dyslipidemia and 3.79 (95% CI 2.83-5.06) for obesity. Conclusion In this study, we addressed the effect of family history as an independent risk factor on the major CRFs for the first time in the region. We observed that the majority of young Emirati adults had a positive family history of CVD-related diseases. Family history showed a strong association with the increased prevalence of CRFs. Additionally, having more relatives with specific diseases was associated with a higher risk of developing CRFs. Identifying people with a history of these conditions can help in early intervention and personalized risk assessments.